Human epidermal growth factor receptor 2-directed therapeutics and their role in changing the natural course of breast cancer - Mark Sliwkowski (Philosophical Transactions of the Royal Society B: Biological Sciences, 2026)
Abstract ErbB/EGFR (erythroblastosis B/epidermal growth factor receptor) family members play a role in driving the growth of various solid tumours. Therapeutic agents directed against two receptor family members, EGFR and human epidermal growth factor receptor 2 (HER2/ErbB2), show meaningful clinical benefit in solid tumours, including breast, lung, colorectal, gastric, head and neck. Clinically approved agents can be divided into three general categories: small-molecule tyrosine kinase inhibitors, monoclonal antibodies and their conjugates. Multiple laboratory studies implicate HER3/ErbB3 and HER4/ErbB4 as potential targets for drug development. Recently, encouraging clinical data were reported for a HER3-directed antibody-drug conjugate, patritumab deruxtecan. Despite the success of the EGFR or HER2 therapies, a significant number of patients will recur with metastases outside the primary tumour site. Notably, several cancers, including breast, lung and melanoma, frequently metastasize to the brain. Unfortunately, conventional therapies may not traverse the blood–brain barrier. Novel approaches to deliver macromolecules across the blood–brain barrier are being developed and show early promising clinical data. This article is part of the discussion meeting issue ‘Epidermal growth factor receptor after 40 years’.